Determinanan kedewasaan usia perkawinan berdasarkan dukungan sosial dan demokratisasi orang tua dalam upaya pencegahan stunting - Tri Sunarsih (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Stunting remains a major public health problem due to its long-term consequences on human resource quality and continues to be one of the national health priorities. Prevention strategies require a comprehensive approach, including improving the maturity of marriage age among premarital adolescents. Social factors, particularly social support and parental democratization, are considered important determinants that influence adolescents’ readiness to enter marriage and contribute to stunting prevention efforts. Purpose: To analyze the determinants of marriage age maturity based on social support and parental democratization among premarital adolescents as an effort to prevent stunting. Method: A quantitative analytic design with a cross-sectional approach involving 260 premarital class participants in Kulon Progo Regency. Samples were selected using simple random sampling. Data were collected using structured questionnaires measuring parental democratization and social support, including family support, peer support, and health worker support. Data were analyzed using univariate analysis, Chi-square test for bivariate analysis, and multiple logistic regression for multivariate analysis. The strength of association was presented using odds ratio (OR) with a 95% confidence interval. Results: The multivariate analysis showed that parental democratization (p=0.000; OR=8.987) and health worker support (p=0.003; OR=5.508) were significant determinants of marriage age maturity. The logistic regression model showed a classification accuracy of 79.6% and explained 50.1% of the variation in marriage age maturity. Family support (p=0.105; OR=2.756) and peer support (p=0.498; OR=0.741) were not statistically significant determinants. Conclusion: Parental democratization and health worker support are dominant factors associated with marriage age maturity among premarital adolescents. Strengthening democratic parenting practices and optimizing the role of health workers may support efforts to improve marriage readiness and prevent stunting. Keywords: Marriage Age Maturity; Parental Democratization; Premarital Adolescents; Stunting Prevention; Social Support.